2022
DOI: 10.3390/digital2030019
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Linked Open Data in Archaeology and Their Realisation in Wikidata

Abstract: In this paper, we introduce Linked Open Data (LOD) in the archaeological domain as a means to connect dispersed data sources and enable cross-querying. The technology behind the design principles and how LOD can be created and published is described to enable less-familiar researchers to understand the presented benefits and drawbacks of LOD. Wikidata is introduced as an open knowledge hub for the creation and dissemination of LOD. Different actors within archaeology have implemented LOD, and we present which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Any place where a network analysis approach might be valid could perhaps be investigated through transformation into a knowledge graph embeddings approach. The use of graph databases in archaeology is gathering some steam (Schmidt et al 2022). Graph databases can be queried (depending on the approach) with query languages such as Cypher or SPARQL, which focus on traversing the graph in order to surface results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any place where a network analysis approach might be valid could perhaps be investigated through transformation into a knowledge graph embeddings approach. The use of graph databases in archaeology is gathering some steam (Schmidt et al 2022). Graph databases can be queried (depending on the approach) with query languages such as Cypher or SPARQL, which focus on traversing the graph in order to surface results.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more familiar to archaeologists is the concept of “linked open data,” which can also be thought of as a knowledge graph in which the entities are anchored to online authority files using the infrastructure of the web itself to represent connections. For an archaeological overview of linked open data, see Schmidt et alia (2022).…”
Section: Knowledge Graph Embedding Models and The Organigrammentioning
confidence: 99%
“…or OpenDataSoft 12 , adopted by the Paris ODP 13 . Ojo et al [37] conducted a comparison of different platforms and concluded that CKAN, DKAN, and Semantic MediaWiki 14 are the most comprehensive options, highlighting their open source nature and easy extensibility.…”
Section: Enabling Technologymentioning
confidence: 99%
“…OD have been used in numerous fields highlighting ODbased smart city applications [10], [11]. They have also been used to develop solutions in many other fields such as digital twins [12], cultural heritage [13], agriculture [14], medicine [15], etc. Even OD has been used in artificial intelligence by providing datasets to train machine learning models [16], [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation